Umar bin Khattab: A Transformative Leader - Ningrum, Ulfia (FALASIFA : Jurnal Studi Keislaman, 2025)
Leadership plays an important role in organizational management. Effective leadership is crucial for achieving desired goals. This study examines the leadership of Umar bin Khattab, the second Amirul Mukminin in Islam, with a focus on his transformative contributions in various sectors such as education, economy, politics, and military. Using a qualitative descriptive approach, this study combines content analysis and literature review. These findings highlight the implementation of Umar bin Khattab's innovative policies, alongside his commitment to justice and the welfare of society. His disciplined and intelligent approach enabled him to build a well-structured governance system centered on serving the needs of the community.